Pressure-Dependent Thermal Network Model for Press-Pack Power Modules with Prognostics of Mechanical Status - Yao Chang; Yu Zhou; Ankang Zhu; Haoze Luo; Wuhua Li; Chushan Li; Francesco Iannuzzo; Xiangning He (CSEE Journal of Power and Energy Systems)
The press-pack power module with multi-chip layout has drawn increasing attention from industry and academia with its thermal analysis becoming an essential issue. However, the pressure-dependent thermal variables, such as thermal contact resistance and thermal coupling resistance, are often neglected. In this paper, a pressure-dependent thermal network model is developed to characterize the thermal performance and mechanical status of press-pack power modules. By including the thermal contact resistance and thermal coupling resistance as the function of pressure, the proposed model ensures a more precise thermo-mechanical evaluation inside the press-pack power module. The influence of pressure on self-heating effects and thermal coupling effects of power modules is studied using the knowledge of elastic mechanics. A press-pack prototype with variable pressure loads is assembled. Then, thermal experiments under different pressures on chips are conducted and the pressure-variable temperature responses of the thermal network are measured. Consequently, the feasibility of the proposed thermal network model is validated. A cost-effective prognostic method on the mechanical status of press-pack power module is also achieved.